Kul´tavyja kamjani Belarusi - Ljaukou, Ernst (Studia mythologica Slavica, 2000)
The article analyses cult stones on the territory of Belarus, among them such types as stones with footprints, stones for protection, officinal- and treasure-stones, petrified people and animals. The stones are known under the following names: the God's footprint, the Holy stone, Volas, Dazhdzboh (Rain-God), Kapavishcha (Sanctuary), Forefather, and others. Even today people make sacrifice (money, flowers, apples) to many of these stones.
Keywords: kamni; kulti; verovanja; Belorusija; 18./20.st.